2016
DOI: 10.1111/jog.13224
|View full text |Cite
|
Sign up to set email alerts
|

Mature cystic teratoma coexisting with clear‐cell carcinoma in the ovary

Abstract: Mature cystic teratoma (MCT) is the most common benign ovarian tumor; clear-cell carcinoma (CCC) is a relatively common malignant ovarian tumor in Japan, but there are few reports on the coexistence of MCT and CCC. Here we report a case of simultaneous MCT and CCC in the ovary and review the relevant literature. The patient was a 49-year-old woman. A 5-cm MCT was found in the left ovary on initial gynecological examination, and she was referred to hospital for treatment because it was expanding. Magnetic reson… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 7 publications
(6 reference statements)
0
4
0
Order By: Relevance
“…When malignant transformation of MCT is diagnosed, it is very important to determine whether the clear cell carcinoma coexists incidentally or that the clear cell carcinoma arises from MCT. So far, three cases of the coexistence of MCT and clear cell carcinoma have been reported [ 25 – 27 ]. However, in those reports, it is not pathologically proven that clear cell carcinomas have arisen from MCT.…”
Section: Discussionmentioning
confidence: 99%
“…When malignant transformation of MCT is diagnosed, it is very important to determine whether the clear cell carcinoma coexists incidentally or that the clear cell carcinoma arises from MCT. So far, three cases of the coexistence of MCT and clear cell carcinoma have been reported [ 25 – 27 ]. However, in those reports, it is not pathologically proven that clear cell carcinomas have arisen from MCT.…”
Section: Discussionmentioning
confidence: 99%
“…Squamous cell carcinoma is the most common malignant transformation in MCT (75% of cases) which are usually moderate to poorly differentiated [16] . Transformation of MCT to clear cell carcinoma is rare and to our knowledge only one case has been reported till now 10 , while three reports of coexistence of MCT and clear cell carcinoma are also there [9,11,12] . Clear cell carcinoma as we know histologically displays several patterns which often occur together.…”
Section: Case Reportmentioning
confidence: 99%
“…Primary squamous cell carcinoma arising from endometriosis of ovary cases were excluded, and cases of malignant transformation from teratoma (endometrioid carcinoma or clear cell carcinoma) were also excluded. A total of three cases were found, and a case report was written in English [83]. The rest of cases were reported in Japanese and hence excluded [84,85].…”
Section: Recurrence and Malignant Transformationmentioning
confidence: 99%
“…The rest of cases were reported in Japanese and hence excluded [84,85]. Shimura et al [83] reported a 71-year-old patient who underwent surgery with a tumor up to 40 cm in the right ovary. The pathologic diagnosis was MCT, endometriotic cyst, clear cell carcinoma, clear cell adenofibroma, and clear cell borderline tumor.…”
Section: Recurrence and Malignant Transformationmentioning
confidence: 99%